The Chinese National Twin Registry: An Update. (8th January 2013) - Li, Liming; Gao, Wenjing; Yu, Canqing; Lv, Jun; Cao, Weihua; Zhan, Siyan; Wang, Shengfeng; Wu, Chaoqun; Hu, Yonghua
Abstract : The Chinese National Twin Registry (CNTR), established in 2001, is the first and largest population-based twin registry in China. Based on the CNTR, a new twin cohort was recruited from 2011 to study the relationship between environmental risk factors and chronic diseases. So far, 33, 874 twin pairs from nine provinces have been recruited, in which hundreds of disease-discordant twin pairs and even thousands of exposure-discordant twin pairs were found in this cohort. The updates of the CNTR will be introduced in detail in this article.